Candle in the dark the story of William Carey - Tew, Tony.; Curtis, A. Kenneth; Pritchard, Mike.; Christian History Institute; Lantern Films and Video; Gateway Films; Vision Video (Firm) (Worcester, Pa. : Distributed by Vision Video, 2005)
Dramatic film of the life and work of William Carey, missionary to India for over 40 years, particularly his struggle against the practice of sati, the burning alive of widows with their husbands' corpses.
Richard Attlee, Lynette Edwards, Julie-Kate Olivier.
Executive producer, Ken Curtis ; producer, Mike Pritchard ; writer, director, Tony Tew.
DVD.
"Many special features including full curriculum"--container.
Keywords: Carey, William, -- 1761-1834.; Missionaries -- India -- Biography; Missions -- India; Baptists -- Missions -- India; India -- Church history